A comparison of contiguous two-level anterior cervical discectomy and fusion using a structural allograft versus a Polyetheretherketone (PEEK) cage: the results of a three-year follow-up - Ing How Moo; Carmen Jia Wen Kam; Maksim Wen Sheng Lai; William Yeo; Reuben Chee Cheong Soh (BMC Musculoskeletal Disorders, 2020)
Abstract Background Allografts and polyetheretherketone (PEEK) cages are the two most commonly used materials in anterior cervical discectomy and fusion (ACDF). However, their effectiveness in two-level ACDF remains controversial. The primary aim of this retrospective study was to compare the clinical and radiological outcomes of two-level ACDF with plate fixation using either a structural allograft or a PEEK cage. Methods From 2010 to 2015, 88 consecutive patients underwent two-level ACDF, of whom 53 received an allograft and 35 patients received a PEEK cage. All PEEK cages were filled with local autografts. All clinical outcomes were prospectively collected before and six months and two years after surgery. Clinical efficacy was evaluated using a visual analogue scale for neck pain and limb pain, the Neck Pain and Disability Score, the Neck Disability Index, the Neurogenic Symptom Score, and the Japanese Orthopedic Association score. Radiological outcomes were assessed preoperatively, immediately after surgery, and at the final follow-up. Results A preoperative comparison revealed no difference between the two patient groups in terms of age, sex, body mass index, smoking status, preoperative symptoms, operation level, or follow-up (mean = 42.8 months). No differences in the improvements in clinical outcomes were observed between the two groups. Both groups showed significant improvement in mean disc height, segmental height, and segmental lordosis postoperatively. The fusion rate for the PEEK cage was 100% at both levels, while the fusion rate for the allograft group was 98.1% at the cephalad level and 94.2% at the caudad level (p > 0.05). Subsidence at the cephalad level occurred in 22.9% (8/35) of segments in the PEEK group and 7.7% (4/52) of segments in the allograft group (p = 0.057). At the caudal level, a higher incidence of cage subsidence was noted in the PEEK group than in the allograft group [37.1% (13/35) versus 15.4% (8/52)] (p = 0.02). Overall, subsidence was noted in 30% (21/70) of the PEEK group and in 11% (12/104) of the allograft group (p <  0.05). Conclusion The use of PEEK cages resulted in a higher rate of subsidence in two-level ACDF than the use of allografts. Two-level ACDF using either allografts or PEEK cages resulted in similar clinical outcomes, radiological improvements in alignment and fusion rates.